Ekses Ketidaktuntasan Pembelajaran Baca Tulis Alquran terhadap Peningkatan Kuantitas Buta Huruf Arab di Kalangan Pelajar SMA/SMK Umum di Kota Bandung - Eni Zulaiha; Busro Busro (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The Excess of the Incomplete Learning of Reading and Writing of Qur'an towards the Increase in the Quantity of Arabic Illiteracy among Public High School / Vocational High School Students in BandungThis research aimed to find the objective condition of AL-Qur’an illiteracy among senior high school or vocational high school students in Bandung and its causes. It used a descriptive qualitative research methodwith observations and questionnaires as data collection instruments. The results showed the following: 1) the literacy rate of AL-Qur’an illiteracy among senior high school or vocational high school students in Bandung reached an average of 13% and who were not good at reading (tahsin) were 80%; 2) There were many factors of less successful in learning AL-Qur’an, either internal or external factors. The conclusion showed the incomplete Baca Tulis Alquran (BTQ or reading and writing ofAL-Qur’an) in Islamic subject learning caused by AL-Qur’an illiteracy among senior high school / vocational high school students in Bandung. Its inadequacy was due to students’ low perception and motivation in the subject. Their low perception and motivation were due to unclear vision and mission of learning because BTQ learning was not the main school program, and it was also not tested at National Exam and Computer Based Test. Hence, the teacher of Islamic subject and its learning implementation were less noticed. The researchers recommend the new and varied BTQ learning designs and competent teachers to achieve religious Bandung